Assessment of the integrity of the noradrenergic nucleus locus coeruleus during normal ageing by neuromelanin‐3T MRI: Neuroimaging / Normal brain aging. (7th December 2020) - Galgani, Alessandro; Lombardo, Francesco; Hana, Hlavata; Daniele, Della Latta; Ghicopulos, Irene; Coi, Alessio; Martini, Nicola; Marchi, Daniele; Keilberg, Petra; Tognoni, Gloria; Siciliano, Gabriele; Ceravolo, Roberto; et al.
Abstract: Background: The pontine nucleus Locus Coeruleus (LC) provides noradrenergic innervation to the whole brain. It is involved in neuronal homeostasis, sleep/wake cycle and in specific cognitive functions. Several data suggest a degeneration of LC in neurodegenerative disorders. Recent post‐mortem studies showed that LC is not affected by ageing (Theofilas et al., 2017, Alzheimers Dement. 13:236‐46). Using a neuromelanin‐sensitive 3 Tesla MRI protocol, we assessed LC integrity in healthy elderly subjects, exploring also the occurrence of age‐related modifications and evaluating any correlation with cognitive performance. Method: 60 healthy volunteers aged 60‐80y, equally distributed by sex and age, underwent 3‐Tesla brain MRI (Signa‐GEH), including neuromelanin (NM)‐sensitive FSE T1‐weighted sequences for LC study, which were evaluated by two independent operators, using a semi‐automatic software (modified from Garcia‐Lorenzo, 2013, Brain, 136:2120‐9). Results were expressed with the parameter VOX, that is the total amount of MRI‐voxels positive for LC‐signal. Then, subjects were submitted to a full neuropsychological assessment, including evaluation of verbal and visuo‐spatial memory, attention and executive functions. A test‐retest reliability verification was performed, comparing the variability intra and inter‐operator. Result: We did not observe any significant age or gender‐related variation of the parameter VOX; no correlation was detectable between VOX values and cognitive tasks performances; our protocol showed a good intra‐ and inter‐observer reproducibility. Conclusion: Our results are in line with recent neuroanatomical post‐mortem data which did not describe any age‐related modification of LC in cognitively healthy subjects; the small variability among subjects we observed for selected cognitive functions did not correlate with significant variations of MRI LC signal. Assessing the LC integrity in healthy elderly subjects is a necessary preliminary step for studies evaluating LC involvement in neurodegenerative disorders, as Alzheimer's Disease, in which LC degeneration might be a key‐point in the pathogenesis (Kelly et al., 2017, Acta Neuropathol Commun. 5:8). (Funding: Ministero della Salute PE‐2013‐02359574; P.I.:FSG).